2023
DOI: 10.1039/d2ja00430e
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-selective post-plasma chemical ionization for enhanced elemental detection of fluorochemicals

Abstract: Elemental analysis of fluorochemicals has received a renewed attention in recent years stemming from increased use of fluorinated compounds. However, fundamental drawbacks of in-plasma ionization have hindered ICPMS applications in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Ideally, new ionization chemistries should be developed to address these areas in a fundamental fashion. For example, we have recently demonstrated that Sc­(NO 3 ) 2 (H 2 O) n + acts as a more selective reagent ion for HF detection . As a result, the HF detection dependence on plasma chemistry is reduced, and tolerance for matrix effects from Cl is improved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, new ionization chemistries should be developed to address these areas in a fundamental fashion. For example, we have recently demonstrated that Sc­(NO 3 ) 2 (H 2 O) n + acts as a more selective reagent ion for HF detection . As a result, the HF detection dependence on plasma chemistry is reduced, and tolerance for matrix effects from Cl is improved.…”
Section: Discussionmentioning
confidence: 99%
“…Interface. An improved design of the post-plasma chemical ionization interface 25 was utilized for better control of plasma sampling. This design was fitted to the entrance of a Q Exactive Orbitrap-MS as illustrated in Figure 1.…”
Section: Chemical Ionizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of inefficient ionisation of F in the Ar ICP-MS was addressed by Tanen et al 58 who developed a post-ICP chemical ionisation method to form BaF + ions. They achieved this using an interface composed of two chambers.…”
Section: Instrumentation Fundamentals and Chemometricsmentioning
confidence: 99%